The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1109/jmems.2015.2477217
|View full text |Cite
|
Sign up to set email alerts
|

3-D Non-UV Digital Printing of Hydrogel Microstructures by Optically Controlled Digital Electropolymerization

Abstract: Abstract-A technique using digital masks without ultraviolet light to rapidly print 3-D biopolymer structures with complex microarchitectures in a microfluidic chip has been demonstrated. In this approach, a customized system is used to project light images on a photoconductive substrate in order to create localized virtual electrodes when an alternating electric field is applied across the fluidic medium in an optically controlled digital electropolymerization chip. Upon these virtual electrodes, the localize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…In recent years, a series of photoresponsive hydrogel‐based functional materials have been developed that show a number of emerging features, such as fluorescent, mechanical, and adhesive properties . However, changing the conductivity of hydrogels by illumination‐mediated ionic migration represents a promising yet challenging photoconductive property that could be applied in many fields, including photodetectors, the simulation of biophotoelectric signals, and light control circuits . Because of the difficulty of modulating the free movement of ions, it seems impossible to achieve photocontrolled ionic conductivity in hydrogels by using a chemical strategy.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, a series of photoresponsive hydrogel‐based functional materials have been developed that show a number of emerging features, such as fluorescent, mechanical, and adhesive properties . However, changing the conductivity of hydrogels by illumination‐mediated ionic migration represents a promising yet challenging photoconductive property that could be applied in many fields, including photodetectors, the simulation of biophotoelectric signals, and light control circuits . Because of the difficulty of modulating the free movement of ions, it seems impossible to achieve photocontrolled ionic conductivity in hydrogels by using a chemical strategy.…”
Section: Methodsmentioning
confidence: 99%
“…Mask-free and non-UV based polymerization and prototyping of high-aspect-ratio 3D hydrogel microstructures, such as poly (ethylene glycol) (PEG)-diacrylate (PEGDA), was demonstrated in an OEK chip [80][81][82][83][84][85].…”
Section: Fabrication and Assembly Of Hydrogel-based Micro/nanostructuresmentioning
confidence: 99%
“…Parallel micro/nanostructures were flexibly patterned onto the chip using optical images. Furthermore, by projecting a series of customdesigned and dynamic optical patterns that served as digital masks, 3D microstructures were fabricated rapidly in a layer-by-layer manner, with their thickness varying from tens of nanometers to hundreds of micrometers [81]. Figure 14.…”
Section: Fabrication and Assembly Of Hydrogel-based Micro/nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on an ODEP chip and system, manipulation and deposition based on other mechanisms such as optically-induced AC electro-osmosis (ACEO), opticallyinduced AC electro-thermal (ACET) flow have been previously discussed [27][28][29]. Recently, we found that the OED process could also be performed and controlled in the ODEP chip, and its applications in patterning hydrogels and other devices have been demonstrated in our previous reports [30,31]. The mechanism of the positive ODEP force and the ACEO force also have the ability to assemble structures by attracting nanomaterials around the optical patterns to form micro structures with specific shapes.…”
Section: Introductionmentioning
confidence: 99%